Intertemporal prosocial choice: The inconsistency puzzle - Marco Islam (Lund University, School of Economics and Management, Department of Economics, 2022)
How does delay in the realization of a prosocial decision affect prosocial choice? This paper first provides a meta-analysis that collects existing evidence on the temporal consistency of prosocial behavior. I show that the evidence on the delay effect on prosocial choice is contradicting but appears reconcilable by a moderating factor: repeated interaction. Motivated by this finding, I conduct an intertemporal donation experiment to closely investigate this moderation effect. I design an experiment that mimics a telephone fundraiser and vary both the timing of the donation (immediate vs. delayed) and the frequency of interaction (one-shot vs. repeated interaction). The results reveal that both under repeated and one-time interaction delayed donations increase relative to immediate donations but the increase is not statistically significant. This evidence suggests that repeated interaction (via telephone) does not provide the conditions for delay to increase prosocial behavior.
Keywords: D64; D90; C91; 330; intertemporal choice; prosocial behavior; charitable giving; repeated interaction